Ethno-botanical study of plants used by Kodava tribes in Kodagu district of Karnataka (Current Horticulture, 2024)
The ethnic knowledge on medicinal value of major plants viz. Justicia wynaadensis, Remusatia vivipara, and Bambusa bambos consumed by Kodava tribes in Kodagu District of Karnataka, India was carried out to preserve the herbal/medicinal plant wealth  and their proper usage, as there is a decline in human expertise to identify and recognize various medicinal plants. Data were  documented using conventional ethnobotanical methods such as interviews and discussion with local populace of Kodava tribals  (headmen, healers, and elderly persons) of the study area using a semi-structured questionnaire comprising information about  plants and their local names, plant parts used, time of usage, method of sample collection and preparation of dishes, their nutritional  and their use in traditional folk medicines, and any other specific comments. The study indicated that J. wynaadensis, locally known  as Maddh toppu or Kurinji Toppu or Aati soppu, undergoes a mysterious transformation in terms of chemical constituents during wet  and dark months of the monsoon, which is responsible for its medicinal values. During Kakkada padinet, Kodava people consume  Maddu Payassa prepared from J. wynaadensis and believe that it generates heat and stabilizes the body temperature, and thus gives  resistance against fever and cold during monsoon season. The R. vivipara is known as Mara Kesa, is used in folk medicine to cure  inflammation, arthritis, to dispel worms and germs for disinfecting the genito-urinary tract. The consumption of newly emerged  bamboo shoots (B .bambos) along with mushrooms is said to balance the body temperatures during heavy rainy days. In summary,  the participants of the study underlined that these underutilized vegetables, major components in traditional dishes, offer enhanced  nutritional and medicinal values when consumed especially during the monsoon season.
Keywords: Ethnic knowledge; Folk medicine; Inflammation; Kodava tribes; Leafy vegetables; Medicinal value